Role of p16INK4A in Replicative Senescence and DNA Damage-Induced Premature Senescence in p53-Deficient Human Cells - Razmik Mirzayans; Bonnie Andrais; Gavin Hansen; David Murray (Biochemistry Research International)
The p16INK4A (hereafter p16) tumor suppressor is encoded by the INK4A/ARF locus which is among the most commonly dysregulated sequences in human cancer. By inhibiting cyclin-dependent kinases, p16 activates the G1-S checkpoint, and this response is often considered to be critical for establishing a senescence-like growth arrest. Not all studies support a universal role for p16 in senescence. Single-cell analysis of noncancerous human fibroblast cultures undergoing senescence as a function of culture age (replicative senescence) has revealed that p16 is not expressed in the majority (>90%) of cells that exhibit features of senescence (e.g., flattened and enlarged morphology coupled with senescence-associated β-galactosidase expression), ruling out a requirement for p16 in this process. In addition, ionizing radiation triggers premature senescence in human cancer cell lines that do not express p16. These observations are made with cells that express wild-type p53, a key mediator of the DNA damage response. In this paper, we examine the growing evidence suggesting a negative regulatory relationship between p16 and p53 and discuss recent reports that implicate a role for p16 in replicative senescence and ionizing radiation-induced premature senescence in human cells that lack wild-type p53 function.